Luther's Topology: Creatio Ex Nihilo and the Cultivation of the Concept of Place in Martin Luther's theology - Mackenzie, Jon (Modern theology, 2013)
This article contends that, although Luther does develop a fascinating concept of the human subject within his writings, he does not make this subjectivity methodologically basic. Instead, Luther locates human subjectivity within a more fundamental framework of "place"—a concept he develops over a span of thirty years, maturing from its earliest appearances, as a corollary of the theologia crucis, into a more expansive framework for his later thinking. After briefly sketching the concept of place within Luther's theology through to its apex—the Genesisvorlesung delivered in the final ten years of Luther's life—the subsequent prominence of the doctrine of creation, particularly the language of creatio ex nihilo, is examined with a view to showing how Luther's theology might be re-placed more constructively within contemporary thinking.